2003
DOI: 10.1097/00004872-200304000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Persistent lowering of arterial pressure after continuous and intermittent therapy

Abstract: This study provides new evidence that combination therapy, not directly targeting the RAS, can be efficacious in persistently reducing MAP off-treatment. Furthermore, we demonstrated that the 6-week treatment with RAS inhibitors induced equivalent persistent changes as a 10-week treatment. That is, the additional 4 weeks of continuous therapy was ineffective in further altering the off-treatment MAP. In contrast, with the intermittent treatment protocol (the 14-week 'drug holiday') a further effect on persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Based on these results, investigations into the mechanisms of antihypertensive drug-induced vascular remodeling in SHR can focus on a time frame spanning days to weeks and not months as has been done previously. In addition, particularly when combined with those of Woolard et al, 9 the results emphasize that treatments that effectively reduce blood pres- …”
Section: Perspectivesmentioning
confidence: 72%
See 2 more Smart Citations
“…Based on these results, investigations into the mechanisms of antihypertensive drug-induced vascular remodeling in SHR can focus on a time frame spanning days to weeks and not months as has been done previously. In addition, particularly when combined with those of Woolard et al, 9 the results emphasize that treatments that effectively reduce blood pres- …”
Section: Perspectivesmentioning
confidence: 72%
“…[1][2][3][4] These effects have been shown in several models of experimental hypertension, including the Prague hypertensive rat 5 and the genetically hypertensive rat, 6,7 although this is best documented in the spontaneously hypertensive rat (SHR). [1][2][3]8,9 The concept that the persistent reduction in MAP and the regression of vascular structure are linked mechanistically has also been widely discussed, although without resolution. 1-4,10 -14 Further, the vascular structural changes that persist off-treatment have been proposed to result from extended inhibition of the trophic actions of angiotensin II, 8,15,16 prolonged reduction in arterial pressure, 16 -18 or from the combined effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into mechanisms by which enalapril and/or rosiglitazone therapy may simultaneously improve the metabolic and hemodynamic phenotype of SHRs, we evaluated endothelial function in MVBs isolated from SHRs after 3-week therapy with drugs or vehicle. Although the doses of rosiglitazone and enalapril that we used in our study are higher than those usually used in humans, the doses that we used are typical for rodent studies (62)(63)(64). Given the large surface area and synthetic capacity of microvascular endothelium, small resistance vessels in the MVBs represent important determinants of plasma levels of endothelium-derived mediators and total peripheral vascular resistance.…”
Section: Discussionmentioning
confidence: 97%
“…This finding indicates that, in SHR, hydralazine given early after birth has a prolonged antihypertensive action similar to that of sympatholytic drugs (14,19) or angiotensin-converting enzyme inhibitor treatment (34). Consistent with this observation, radio-telemetric studies have shown that hydralazine with a diuretic and a Ca 2ϩ antagonist lowers arterial pressure for several weeks beyond cessation of drug administration in adult SHR (40). The different potency of these treatments to induce chronic changes in renal function that contribute to the maintenance of the arterial pressure reduction becomes apparent in transplantation experiments (14,34).…”
mentioning
confidence: 58%